MANAGEMENT OF INHIBITORS IN HEMOPHILIA - Gaye Kalacı Katayıfçı (Hematology, Transfusion and Cell Therapy)
Introduction: The improved understanding of Acute Myeloid Leukemia (AML) pathobiology has led to significant advances in treatment options. AML is a highly heterogeneous disease, with clinical, morphological, cytogenetic, and molecular variability, which is crucial for developing targeted therapies within different subgroups.The ''7 + 3'' regimen (7 days of cytarabine and 3 days of daunorubicin) remains the standard, but its long-term efficacy is limited, with remission rates below 40% in younger, fit patients. In contrast, for older patients or those unsuitable for intensive chemotherapy, median survival is approximately 9 months, and 5-year survival rates are under 10%. Treatment strategies are typically tailored, with intensive chemotherapy preferred for younger/fit patients, and low-intensity therapies for older/unfit patients.This section reviews emerging targeted treatment options. Antibody-Drug Conjugates (ADCs): Gemtuzumab ozogamicin (GO), a CD33-targeted ADC combined with high-dose cytarabine, has increased survival rates from 50% to 75-80%. IMGN779, a novel anti-CD33 ADC, is highly effective against AML cells, including those with adverse molecular abnormalities, and its sensitivity is correlated with CD33 expression levels.AVE9633, another anti-CD33-maytansin conjugate, has shown promising results in Phase I trials with relapsed/refractory AML patients. Targeting CD123 with ADCs and exploring NK cell therapies offer hope for AML with measurable residual disease (MRD) or high-risk forms. Bispecific T-Cell Engagers (BiTEs): Bispecific T-cell engagers (BiTEs), such as AMG330 and AMG673, redirect T-cells or NK cells to AML cells, yielding a 20-30% response rate, though they are associated with significant side effects like cytokine release syndrome. These therapies may benefit MRD-positive AML patients in remission. T-cell immunotherapies, including flotetuzumab (FLZ), enhance T-cell activation and MHC-independent killing of AML cells, showing promise in overcoming chemotherapy resistance. Checkpoint Inhibitors: Immune checkpoint inhibitors targeting PD-1/PD-L1 are being explored in AML and Myelodysplastic Syndromes (MDS). Preclinical studies suggest potential benefits, but challenges remain in identifying biomarkers and optimizing combination therapies. Magrolimab, an anti-CD47 monoclonal antibody, has shown a 71% response rate and 45% complete remission (CR) when combined with azacitidine in TP53-mutant AML. CAR-T Cell Therapies: The success of CAR-T cell therapies in hematologic cancers has sparked interest in applying this approach to AML. Preclinical studies show that CAR-T cells targeting AML surface proteins, such as CD33 and CD123, can effectively eliminate AML cells. However, off-target toxicity due to antigen expression on healthy stem cells remains a concern. NK Cell-Based Therapies: Natural killer (NK) cells are being explored as an alternative to allogeneic cell therapies. NK cells can recognize and kill AML cells without causing graft-versus-host disease or cytokine release syndrome, offering a potentially safer treatment approach. Conclusion: In conclusion, with accumulating data, new treatment standards are being developed for AML, particularly for younger and older patients, including induction, consolidation, hematopoietic stem cell transplantation (HSCT), and maintenance therapy.